Le film de mobilisation centrasiatique - Valérie Pozner (Conserveries Mémorielles)
Far from the full-length feature films generally studied in the works dedicated to war propaganda on the screen, this article examines film production specifically launched for Centrasiatic population on the home front, or for the soldiers from these republics. Of modest ambition, generally short, made with what was at hand by evacuated film-makers, these movies appealed to the local myths and to the major figures of the national pantheon. They also embody the main values of the Soviet motherland. This little set of motives was recycled in various genra (feature shorts, musicals, documentaries) which are analyzed here on the example of the production of the main Soviet studio during the World War II, that of Alma-Ata.